Compensation of actuator delay and dynamics for real time hybrid structural simulation. - Ahmadizadeh, M.
Compensation of delay and dynamic response of servo-hydraulic actuators is critical for stability and accuracy of hybrid experimental and numerical simulations of seismic response of structures. In this study, current procedures for compensation of actuator delay are examined and improved procedures are proposed to minimize experimental errors. The new procedures require little or no a priori information about the behavior of the test specimen or the input excitation. First, a simple approach is introduced for rapid online estimation of system delay and actuator command gain, thus capturing the variability of system response through a simulation. Second, an extrapolation procedure for delay compensation, based on the same kinetics equations used in numerical integration procedures is examined. Simulations using the proposed procedures indicate a reaction in high frequency noise in force measurements that can minimize the excitation of high frequency modes. To further verify the effectiveness of the compensation procedures, the artificial energy added to a hybrid simulation as a result of actuator tracking errors is measured and used for demonstrating the improved accuracy in the simulations.
Keywords: Hybrid simulation; Pseudodynamic experiment; Delay compensation; Actuator dynamics